Interactive learning in Python - Xia, Chenguang (Nanyang Technological University, 2022)
In the world of programming languages, Python is almost always ranked as the most popular programming language for beginners. Reasons include its simplicity, comprehensiveness and universality. Most people learning Python actually do not have a programming background and it is very important for them to choose suitable ones from various learning resources available. This project aims to equip learners from all backgrounds with basic Python knowledge through three sub-projects, which are week-by-week assignments that need accomplishing. On a weekly basis, they will learn from the most basic variable definitions to a more complex one like exception handling with increasing difficulty. The projects are especially designed for beginners with no prior learning experience of Python or any other language and they are expected to succeed in building programs that relate to our daily life and are truly useful and practical.